The Influence of Organizational Culture, Leadership Style and Competence on Employee Performance at the Human Resources Development Agency (BPSDM) of the Ministry of Home Affairs of the Republic of Indonesia - Andi Pitono*; Halilul Khairi; Ario Ario (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Researchers took the title The Effect of Organizational Culture, Leadership Style and Competence on Employee Performance at the Human Resources Development Agency (BPSDM) of the Ministry of Home Affairs of the Republic of Indonesia. The number of samples was 221 respondents. The analysis method used is descriptive quantitative using SPSS. The results showed that 1) Organizational culture is able to influence employee performance at BPSDM Kemendagri RI. The stronger the organizational culture at BPSDM Kemendagri RI, the higher the employee performance; 2) Leadership style is able to influence employee performance at BPSDM Kemendagri RI. The better the leadership style at BPSDM Kemendagri RI, the higher the employee performance; 3) Competence is able to influence employee performance at BPSDM Kemendagri RI. The higher the competence of employees at BPSDM Kemendagri RI, the higher the employee performance.